Machine Learning for Prediction of Outcomes in Cardiogenic Shock - Rong, Fangning; Xiang, Huaqiang; Qian, Lu; Xue, Yangjing; Ji, Kangting; Yin, Ripen (Frontiers in Cardiovascular Medicine, 2022)
Objective: The management of cardiogenic shock (CS) in the elderly remains a major clinical challenge. But existing clinical prediction models have not performed well in assessing the prognosis of elderly patients with CS. The aim of the study is to build a predictive model, which could better predict the 30-day mortality of elderly patients with CS. Methods: We extracted data from the Medical Information Mart for Intensive Care III version 1.4 (MIMIC-III) as training set and data of validation sets were collected from the Second Affiliated Hospital and Yuying Children’s Hospital of Wenzhou Medical University. Three models including the cox regression model, the LASSO regression model and the CoxBoost model were be established using the training set. Through the comparison of area under receiver operating characteristic curve (AUC), C index, net reclassification improvement (NRI), integrated discrimination improvement (IDI) and median improvement in risk score, the best model was selected. Then for external validation, compared the best model with simplified acute physiology score II (SAPSII) and the CardShock risk score. Results: A total of 919 patients were included in the study, of which 804 patients were in the training set and 115 patients were in the verification set. Using the training set, we built three models: the cox regression model including 6 predictors, the LASSO regression model including 4 predictors and the CoxBoost model including 16 predictors. Among them, the CoxBoost model had good discrimination (AUC: 0.730; C index: 0.6958 (0.6657, 0.7259)). Compared with the CoxBoost model, the NRI, IDI and median improvement in risk score of other models were all < 0. In the validation set, the CoxBoost model was also well-discriminated (AUC: 0.770; C index: 0.7713 (0.6751, 0.8675)). Compared with the CoxBoost model, the NRI, IDI and median improvement in risk score of SAPSII and the CardShock risk score were all < 0. And we constructed dynamic nomogram to visually display the model. Conclusion: In conclusion, this study showed that in predicting the 30-day mortality of elderly CS patients, the CoxBoost model was superior to cox regression model, LASSO regression model, SAPSII and the CardShock risk score.